Understanding the Trends in Welding of Copper and Steel - Maji, Pabitra; Meitei, R. K. Bhogendro; Ghosh, Subrata Kumar (U.Porto Journal of Engineering, 2022)
Copper-steel welded joints are now used widely in heat exchangers, piping and power generation industries. Owing to their different thermal characteristics, sound welding of the pair is a challenging task. Extensive research is carried out to achieve successful welding of copper and steel. This article presents an insight into the works done on the joining of copper and steel by various techniques. The microstructural modifications in different approaches are critically presented. Mechanical properties of joints obtained through different techniques are compared.